1996
DOI: 10.1002/bjs.1800830527
|View full text |Cite
|
Sign up to set email alerts
|

No obvious advantages for thoracoscopic two-stage oesophagectomy

Abstract: Thoracoscopically assisted Ivor-Lewis oesophagectomy potentially combines the pulmonary advantages of transhiatal oesophageal dissection, with the visibility and control permitted by thoracotomy. This study reviewed 17 patients who underwent this procedure with an intrathoracic anastomosis. Five patients required conversion to thoracotomy, four because of technical difficulties with the anastomosis. After operation 13 patients had radiological evidence of atelectasis, six developed a left pleural effusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Many have described the feasibility of the technique, and a few have reported an advantage over open surgery. However, initial results with the thoracoscopic approach did not show a real benefit over the open approach, in particular due to a high number of pulmonary complications [31,32,33,34,35,36,37]. …”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Many have described the feasibility of the technique, and a few have reported an advantage over open surgery. However, initial results with the thoracoscopic approach did not show a real benefit over the open approach, in particular due to a high number of pulmonary complications [31,32,33,34,35,36,37]. …”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…This procedure proved to be feasible and even superior to open surgery. Nevertheless, the irst outcomes using this approach were not signiicantly beter than those obtained with the open approach, mainly as a result of the great number of pulmonary complications [36][37][38]. However, a few medical research centers in Japan found a new stimulus.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…According to some reported series (Dexter et al, 1996;Law et al, 1997), the survival rate for patients with esophageal carcinoma undergoing VATS esophagectomy has results similar to those for patients undergoing transthoracic esophagectomy. However, some other series reported that the pulmonary complications cannot be effectively decreased by using VATS approach (Nagawa et al, 1994;Robertson et al, 1996;Gossot et al, 1995). Therefore the interest in VATS esophagectomy seems to decline throughout the USA and Europe, but is still actively tried in some series in Japan and Asia (Akaishi et al, 1996).…”
Section: In Esophageal Diseasesmentioning
confidence: 99%